ANALISIS RASIO APBD KABUPATEN POHUWATO SEBAGAI ALAT UNTUK MENGUKUR KINERJA PEMERINTAH DAERAH (Studi Penelitian Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Pohuwato) - Sulaiman Sulaiman (AkMen JURNAL ILMIAH, 2014)
The research problem is " How Local Government performance Pohuwato in preparing and implementing the budget in terms of financial independence ratio, the ratio of the effectiveness and efficiency of revenue , growth ratio and the ratio of recurrent and development expenditure against budget. independence ratio Pohuwato in 2013, which is 186.29 % , it was explained that the ability Pohuwato to be able to finance all forms needs in 2014 is far from enough . Effectiveness ratio of 186.86 % menandahkan government 's performance in managing the resources that have the potential is very effective even exceed the standards by 86.29 % . Pohuwato routine expenditure ratio in 2013 that the amount of 11.34 % is very small . And the ratio of regional development Pohuwato in 2013 that the amount of 14.19 % gives an overview of the ability of local governments to allocate APBDnya in 2013 is very low